Effects on The Human Environment and Plants Desert Dusts - Bagci, Harun Resit; Sengun, M. Taner (Marmara Univ, 2012)
In last years, with help of the work of scientists, it has discovered what happened by the desert dusts which some 20 million tones of desert dust being moved by the winds from some areas around of the Turkey's close environs such as; Primarly Sahara, Iran, Syria and Arabian deserts into to the Turkey. Winds which takes of from the desert through the thin dust particles into to the atmosphere whose sizes can be expressed with microns being transported till the remote regions. At the same time, it leaves various effects on the environment where those dusts leaves deposition as well as Human and Vegetation life too. All of these reasons, puts forth that, deserts are not insignificant piles of sand and even they got an important positive and negative function in natural systems too. As the desert dust trigers sine diseases of humans such as asthma and migraine, also causes some primar respiratory diseases to appear as well as other health disorders too. Moreover, It worsens daily life as it also causes disruption of some transportation activities, touristic and economic actvities and also makes difficult to breath the air what we use, as it reduces its quality. Desert dust which falls on plants as dry as they was or through rainfalls has some good effects such as; cultivating plants, accelerating development of plants with some minerals. But also there has some effects are negative as covering survaces of the leaves and blocking their stomata which is neccessary for photosynthesis, and preventing their respiration. In this work, it will be concentrated on what kinds of effects does the desert dust has got on human environment and plants.
Keywords: Desert Dust; Sahara; Deserts; Ecology; Vegetation